Managemen Kepemimpinan Kepala Madrasah dalam Meningkatkan Mutu Pendidikan di MTs Kesuma LKMD Namorambe - Neliwati Neliwati; Uswatun Hasanah; Retno Pringadi (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2022)
This research was conducted in order to find out how the principal's management in advancing education in the private Madrasah Tsanawiyah Kusuma LKMD namorambe. In terms of the progress of management in the Madrasah, it will be seen how leadership management has been implemented by the madrasah leadership to improve the quality of education in the madrasa. Approach to research in the form of qualitative. the way researchers collect sources of data acquisition with question and answer techniques, documentation and observation. The research stages in analyzing the data use several stages which are usually applied to the Miles and Habermann model such as first collecting data, reducing data, presenting data and concluding data. This is the basis in a study of how the leader advances his school to advance his education from the previous state to the future state, it is seen that it is far behind with public schools in the area. schools began to make improvements and evaluation evaluations so that the principal who was able to improve the quality of education and win the trust of the community to send their children to the school. The findings and conclusions of the study indicate that leadership management is carried out by the first madrasah principal, the madrasah principal plans steps by establishing KKG and MGMP activities, the two madrasah principals also plan structured POAC steps in the mission to improve the quality of education in the school.